Annual Plan 1998-99 Volume I Government of Karnataka - Planning Commission (Planning Commission, 1998)
The Planning Commission is yet to hold discussions regarding the outlay for the Annual Plan 1998-99. The budgeted outlay is Rs.5353 crores. Thus there is an increase of 24% over the revised approved outlay of 1997-98 and 18% over the budgeted outlay. The district Plan for 1998-99 has been fixed at Rs.732 crores. The outlay for externally aided projects in 1998-99 is Rs.503.25 crores. Under the Special Component Plan Rs.282.96 crores have been earmarked for the welfare of Scheduled Castes and Rs.50.25 crores for the Scheduled Tribes under the Tribal Subplan.
Government of Karnataka